PKM Penanaman Konsep Dasar Penjumlahan dan Pengurangan Pecahan pada Siswa- Siswi Kelas III di SD GMIT Abangiwang Kecamatan Pantar Timur Kabupaten Alor Tahun 2021 - Melki Imamastri Puling Tang; Yermia S. Wabang; Abraham Puling Tang (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Research through community service (CS) in Bunga Bali village, Pantar Timur sub-district, Alor. PKM instilling the basic concepts of addition and subtraction of fractions in 3rd grade students of SD GMIT Abangiwang is carried out with the aim of finding out the extent of students' knowledge of fractions, whether the denominator is the same or the denominator is different. This PKM activity offers planting the basic concept of multiplication as a reference in understanding fractions. In this PKM, it was found that there was an increase in students' understanding of mathematics, especially fractions in simple fractions, while in fractions whose denominators were not the same, it was necessary to emphasize to students to study harder. The average test result is 61.54% in the sufficient category. Factors causing difficulties in solving simple fractions based on the results of interviews with third grade homeroom teachers generally include interest and motivation, teacher factors, environmental factors, teacher factors, infrastructure factors, environmental factors, and the need for discipline during teaching and learning activities. Some of the 3rd grade students of SD GMIT Abangiwang still find it difficult to memorize multiplications from 1 to 10. This makes it difficult for students. This makes it difficult for them in the section on equating 'fractions with different denominators'. The researcher offers teachers in the field of study that they need to strengthen the basics of multiplication before discussing fractions material.